Truth and the ethics of criticism - Norris, Christopher (Manchester University Press ; Distributed exclusively in the USA and Canada by St. Martin's Press, 1994)
This text is a reply to some of the more doctrinaire beliefs that pass for "radical" thinking. For the most part, Norris argues, these ideas are based on a false understanding of crucial episodes in their own pre-history.